Improving gas/particle flow deflection and asymmetric combustion of a 600 MWe supercritical down-fired boiler by increasing its upper furnace height. (15th May 2017) - Kuang, Min; Zhu, Qunyi; Ling, Zhongqian; Ti, Shuguang; Li, Zhengqi
Abstract: A solution characterized by lengthening its short upper furnace was put forward for improving the gas/particle flow deflection and asymmetric combustion within a 600 MWe supercritical down-fired boiler. Based on the present design dimensionless upper furnace height C H 2  = 0.864, upper furnace was lengthened in turn to C H 2  = 1.00, 1.125, and 1.263 so as to form four comparable settings. Accordingly, cold-modeling gas/particle flow experiments and numerical simulations on coal combustion were performed at these settings for confirming the solution and meanwhile recommending a reasonable C H 2 setup. Moreover, real-furnace measurements, used to confirm the numerical simulation validity, were carried out under normal full load. Results at the design setting ( C H 2  = 0.864) show shat a severely deflected gas/particle flow field appears, with (i) the downward gas/particle flow penetrating much deeper in the front-half side than in the rear-half side and (ii) the upward flow fully deflecting towards the front-half side. Consequently, a bad asymmetric combustion pattern with gas temperatures being much higher in the rear-half side than in the front-half side (temperature gap reaching about 300–600 °C) develops, generating poor burnout and high NO x emissions. Additionally, the simulated results are consistent well with the acquired real-furnace data. In comparison with cold-modeling gas/particle flow experiments, the simulated downward gas/particle flow penetrates clearly shallower in a hot environment. Lengthening upper furnace apparently weakens both the experimental and simulated flow-field deflection and meanwhile improves the asymmetric gas velocity distribution in the upper furnace. As C H 2 increases to 1.125 and 1.263, both the experimental and simulated flow-field symmetries are acceptable, accompanied by symmetrical gas velocity distribution in the upper furnace, improved burnout rate, and lowered NO x emissions. A comprehensive consideration of symmetrical combustion, high burnout rate, relatively low NO x emissions, and controlled cost for lengthening upper furnace suggests that a reasonable C H 2 should be set at 1.125. Highlights: Lengthening upper furnace was used to improve down-fired boiler's asymmetric combustion. The solution's availability was experimentally and numerically confirmed. A reasonable upper furnace height was recommended for new down-fired boiler designs.